PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PEMADAM KEBAKARAN KOTA BOGOR - Sandi Sandi; Sintia Siti Rohmah (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
Fire Department is one element of public service in bogor city that has the main task of carrying out the task of prevention and management of fire hazards. Every company or agency is required to be able to optimize and manage human resources, poor work environment and low employee motivation can result in employee performance becomes not optimal. To improve employee performance, a good work environment is needed in order to create a comfortable, safe, and conducive work atmosphere supported by the facilities and infrastructure owned. The regression test results showed that 66.8% of bogor fire department employees' performancefactors were explained by work environment and work motivation while the remaining 33.2% were explained by other factorsnot studied in this study. While Test F showed that independent variables consisting of work environment and work motivation simultaneously significantly affect the performance of bogor city fire department employees with the results of analysis F count = (68,309) > Ftable = (3,138). Test result t showed the variable motivation of work analysis results tcalculate (8,430) where ttable (1.997) then partially the variable significantly affects the performance of employees while the work environment variable shows the results of tcount (1,326), where ttable (1.997) then partially the variable does not significantly affect the Bogor City Fire Department. It can be explained that the most dominant variable in the Bogor City Fire Department is the motivation of work.